Pengaruh Produk, Harga, Lokasi dan Promosi Terhadap Keputusan Pembelian di D&D Chicken and Burger Sumobito Jombang - Mahmud Arief Annahdy (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
The development of the culinary industry has caused changes in people behavior, this has encouraged companies to continue to innovate in terms of gaining market share. These innovations are related to strategies which include product, price, place, and promotion which will be able to attract consumers to make purchasing decision. This study aims to determine the effect of the product, price, place, and promotion on purchasing decisions at D&D Chicken and Burger Sumobito Jombang. The result method used in this research with analytical techniues using mltiple linier analysis. The population in this study were consummers who made purchases at D&D Chicken and Burger Sumobito Jombang with a total sample of 50 respondents. The result of this study indicate that product, price, place, and promotion variables have a significant effect on purchasing decisions both partially and simultaneosly and the most influential variable is the promotion variable.